State preparation by shallow circuits using feed forward - Harry Buhrman; Marten Folkertsma; Bruno Loff; Niels M. P. Neumann (Quantum)
Fault tolerant quantum computers repetitively apply a four-step procedure: First, perform a few one and two-qubit quantum gates. Second, perform a syndrome measurement on a subset of the qubits. Third, perform fast classical computations to establish if and where errors occurred. And, fourth, correct the errors with a correction step. The next iteration applies the same procedure with new one and two-qubit gates. Even though current error-rates prohibit this procedure to work and fault tolerant quantum computing remains a distant goal, the same procedure can already prove useful today. In this work we make use of this four-step scheme not to carry out fault-tolerant computations, but to enhance short, $constant$-depth, quantum circuits that perform 1 qubit gates and $nearest-neighbor$ 2 qubit gates.